The Influence of Folklore in the Formation of Local Cultural Values: A Phenomenological Approach - Ningsih, Elisa Pitria; Rizki, Silfia Novita (Kamara Journal, 2024)
Folklore has become an integral part of a society's cultural heritage. This study aims to explore the influence of folklore in the formation of local cultural values using a phenomenological approach. The research method used was interviews and data analysis. The data collected was analyzed using a phenomenological approach to understand the subjective experiences of individuals in understanding and responding to folklore. The results showed that folklore has a significant role in shaping local cultural values. Respondents revealed that folklore is not only a medium to convey these values, but also an integral part of cultural identity. The diversity of folklore reflects the diversity of cultural values in the community. In addition, this study highlights the role of the individual in interpreting folklore. Individual subjective experiences play an important role in how folktales are understood and internalized. Contextual factors such as oral traditions, cultural rituals and social structures also influence the way folktales are conveyed and received by the community. Implications of this research include the importance of understanding the role of folklore in the education of local cultural values and in cultural heritage preservation efforts. With a better understanding of the influence of folklore, more effective educational programs and more targeted cultural preservation efforts can be designed.